Towards Understanding and Editing the Appearance of Translucent Materials - Lanza, Dario; Masia, Belen; Jarabo, Adrian (Jornada de Jóvenes Investigadores del I3A, 2023)
In computer graphics, the ability to edit and manipulate material is crucial for creating realistic and believable images. While this ability has always been related to the film and video-games industries, lately more and more product companies want to let their users customize their own products, before buying. Moreover, the recent advances in 3D printing technologies follow this trend. In this context, the usual tools for editing complex materials need to be revised, to simplify the editing phase for novice users. Therefore, we focus on translucent materials, a class of materials that is widely present in the physical world that surrounds us and encompasses both natural substances like food or human skin, as well as synthetic materials such as plastic or jade. While multiple models for translucent materials exist, understanding how we perceive translucent appearance, and how it is affected by illumination and geometry, remains an open problem. In this study, we investigate how accurately human observers can estimate the density of translucent objects under static and dynamic illumination conditions. Surprisingly, our findings suggest that dynamic illumination may not be essential for accurately assessing the nature of translucent materials.